1979
DOI: 10.1111/j.1476-5381.1979.tb10839.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Guinea‐pig Lymphocyte Activation by Histamine and Histamine Analogues

Abstract: I The incorporation of [3H]-thymidine into guinea-pig lymphocytes stimulated by a plant lectin (concanavalin A), soluble antigen (tuberculin (P.P.D.)) and syngeneic hepatoma cells, was partially inhibited (50%) by histamine in vitro. 2 The effect of histamine on both mitogen and antigen dose-response curves suggests a non-competitive, probably physiological antagonism.3 The inhibitory dose range of histamine lay between 10 nm and 30 AM with an ID50 of approximately 400 nM. 4 The potency order for histamine ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1981
1981
1987
1987

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…We have confirmed the finding (Wang & Zweiman, 1978;Beets & Dale, 1979;Brostoff et al, 1980;Ogden & Hill, 1980) The following five findings from the data summarized in Table 1 were found to be inconsistent with the view that the inhibitory effects of histamine-related compounds on lymphocyte proliferation were mediated via H,-or H2-receptors. Firstly, N-3-methylhistamine, which is inactive on conventional histamine receptors (Ganellin, 1980), was as active as histamine in inhibiting lymphocyte transformation in the same concentration range (10 4-10-3M).…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…We have confirmed the finding (Wang & Zweiman, 1978;Beets & Dale, 1979;Brostoff et al, 1980;Ogden & Hill, 1980) The following five findings from the data summarized in Table 1 were found to be inconsistent with the view that the inhibitory effects of histamine-related compounds on lymphocyte proliferation were mediated via H,-or H2-receptors. Firstly, N-3-methylhistamine, which is inactive on conventional histamine receptors (Ganellin, 1980), was as active as histamine in inhibiting lymphocyte transformation in the same concentration range (10 4-10-3M).…”
Section: Resultssupporting
confidence: 52%
“…In the present experiments, the effect of cimetidine or metiamide on histamineinduced inhibition was equivocal (data not shown). These H2-receptor antagonists have been found to augment mitogenesis in the absence of exogenous histamine (Beets & Dale, 1979;Gifford, Stephen, Hatfield & Schmidtke, 1980) and this effect complicates the interpretation of the reversal of inhibition by histamine-related compounds. Nevertheless, the possibility remains that human mononuclear cells bear H2-receptors concerned with other functional activities, such as the inhibition of synthesis of complement components (Lappin & Whaley, 1980) and the generation of soluble factor(s) that suppress lymphokine production (Rocklin, 1977).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include the autacoid, histamine, (Wang & Zweiman, 1978;Beets & Dale, 1979) histamine analogues (Vickers et al, 1980;Gordon et al, 1981) and chloroquine and its congeners (Hurvitz & Hirschhorn, 1965;Trist & Weatherall, 1981). It has been suggested that histamine produces its effects by an action on an H2-receptor (Wang & Zweiman, 1978), though adequate pharmacological evidence for this is difficult to obtain (Beets & Dale, 1979).…”
Section: Intoductionmentioning
confidence: 99%